Chemical Constituents and Relative Nutritive Value of Bromus unioloides B.H.K. of Kumaun Hills at Different Stages of Development - Dhami, K.S.; Pant, C.S. (Asian Journal of Chemistry, 2016)
Chemical investigation of indigenous fodder grass, viz; Bromus uniolodes B.H.K. of Nainital was carried out at different stages of development from July to October 2000 to assess its relative nutritive value as it is commonly used as green fodder by local people during monsoon season and also stored as hay for feeding the cattle during dry witer and summer seasons. This grass was found to containing sufficiently high level of chemical constituents, viz., protein, ether extract extract (crude fat), sugars, ash and minerals and hence is assessed as a good quality fodder.